Nonlinear multiplicative dendritic integration in neuron and network models - Zhang, Danke; Li, Yuanqing; Rasch, Malte J.; Wu, Si (Frontiers in Computational Neuroscience, 2013)
Neurons receive inputs from thousands of synapses distributed across dendritic trees of complex morphology. It is known that dendritic integration of excitatory and inhibitory synapses can be highly nonlinear in reality and can heavily depend on the exact location and spatial arrangement of inhibitory and excitatory synapses on the dendrite. Despite this known fact, most neuron models used in artificial neural networks today still only describe the voltage potential of a single somatic compartment and assume a simple linear summation of all individual synaptic inputs. We here suggest a new biophysical motivated derivation of a single compartment model that integrates the nonlinear effects of shunting inhibition, where an inhibitory input on the route of an excitatory input to the soma cancels or ``shunts'' the excitatory potential. In particular, our integration of nonlinear dendritic processing into the neuron model follows a simple multiplicative rule, suggested recently by experiments, and allows for strict mathematical treatment of network effects. Using our new formulation, we further devised a spiking network model where inhibitory neurons act as global shunting gates, and show that the network exhibits persistent activity in a low firing regime.